2016
DOI: 10.1093/femsle/fnw056
|View full text |Cite
|
Sign up to set email alerts
|

Gliding motility driven by individual cell-surface movements in a multicellular filamentous bacteriumChloroflexus aggregans

Abstract: Chloroflexus aggregans is an unbranched multicellular filamentous bacterium having the ability of gliding motility. The filament moves straightforward at a constant rate, ∼3 μm sec(-1) on solid surface and occasionally reverses the moving direction. In this study, we successfully detected movements of glass beads on the cell-surface along long axis of the filament indicating that the cell-surface movement was the direct force for gliding. Microscopic analyses found that the cell-surface movements were confined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 15 publications
2
9
0
Order By: Relevance
“…Chloroflexales bacteria also possess extracellular appendages such as pili. Long pili have been previously reported in C. aggregans and C. islandicus (Fukushima, 2016;Gaisin et al, 2017). Here, we show that they were also present in R. castenholzii and "Ca.…”
Section: Pili and Receptor Arraysupporting
confidence: 81%
See 2 more Smart Citations
“…Chloroflexales bacteria also possess extracellular appendages such as pili. Long pili have been previously reported in C. aggregans and C. islandicus (Fukushima, 2016;Gaisin et al, 2017). Here, we show that they were also present in R. castenholzii and "Ca.…”
Section: Pili and Receptor Arraysupporting
confidence: 81%
“…It resembled typical bacterial chemoreceptor arrays (Briegel et al, 2009). Previously, Fukushima et al suggested that C. aggregans was capable of aerotaxis (Fukushima, 2016), and a chemotaxis system in Chloroflexales has been predicted by genomic analysis (Wuichet and Zhulin, 2010). These previous findings and the images of chemoreceptor-like arrays presented here show that Chloroflexales bacteria are adapted to active translocation in their environment.…”
Section: Pili and Receptor Arraysupporting
confidence: 79%
See 1 more Smart Citation
“…These Tepidiforma isolates are the only three members of the Chloroflexota known to possess flagella. Many cultivated members of the Chloroflexota are considered non-motile (e.g., 7,33,34 ), although gliding motility in this phylum is well known, particularly in the filamentous Chloroflexia 9,[35][36][37][38] . Despite these observations based on isolates of Chloroflexota, environmental genomics studies have improved representation of the diversity across the phylum and revealed flagellar gene clusters in some Chloroflexota genomes 16,35,[39][40][41] .…”
Section: Dehalococcoidiamentioning
confidence: 99%
“…Wartel, Brochier-Armanet, & Mignot, 2015;Mercier & Mignot, 2016;Nan, McBride, Chen, Zusman, & Oster, 2014) typified by the A motility of Myxococcus xanthus (Figure 1; type 3) (Agrebi et al, 2015;Mercier & Mignot, 2016;Nan et al, 2014), the gliding motility of Bacteroidetes (Figure 1; type 4) (McBride & Nakane, 2015;Nakane, Sato, Wada, McBride, & Nakayama, 2013;Wada, Nakane, & Chen, 2013) represented by Flavobacterium johnsoniae, and the surface motion of thermophilic filamentous bacteria Chloroflexus aggregans classified as phylum Chloroflexi (Figure 1; type 5) (Fukushima, Morohoshi, Hanada, Matsuura, & Haruta, 2016;Hanada, Shimada, & Matsuura, 2002). Spirochete swimming is a variation of the flagellar swimming described above, but achieves a smooth motion by placing flagella inside the outer membrane, in the periplasmic space (Figure 1; type 1b) (Charon et al, 2012;Charon & Goldstein, 2002;Li et al, 2000;Takabe, Kawamoto, Tahara, Kudo, & Nakamura, 2017).…”
mentioning
confidence: 99%